2022
DOI: 10.1177/13623613221138690
|View full text |Cite
|
Sign up to set email alerts
|

Association of labor epidural analgesia exposure with long-term risk of autism spectrum disorder in offspring: A meta-analysis of observational studies

Abstract: To investigate the association between labor epidural analgesia exposure and the risk of autism spectrum disorder in offspring, this meta-analysis reviewed relevant literature from Medline, Cochrane Library, Google Scholar, and EMBASE databases from inception to May 2022 to evaluate the overall adjusted risk of autism spectrum disorder in offspring (primary outcome) and adjusted risks of autism spectrum disorder focusing on sibling-matched data, children who were delivered vaginally, and duration of labor epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…However, upon accounting for potential confounders, the effect diminished, yet remained statistically significant [hazard ratio 1.13, 95% CI, 1.03 to 1.25, and hazard ratio 1.11, 95% CI, 1.06 to 1.165] 16 . Nevertheless, when only studies using a sibling-matched design were analysed, this meta-analysis concluded that there was no significant association (hazard ratio 1.07, 95% CI, 0.99 to 1.16), 13,16 whereas another demonstrated a significant association in sibling-matched designed studies [hazard ratio 1.10, 95% CI, 1.02 to 1.18], 13 with, however, no dose–response effect. It was concluded that the small statistically significant association between LEA and ASD may be elucidated by selection bias and residual (unmeasured) confounders, such as genetic factors 16 …”
mentioning
confidence: 94%
See 3 more Smart Citations
“…However, upon accounting for potential confounders, the effect diminished, yet remained statistically significant [hazard ratio 1.13, 95% CI, 1.03 to 1.25, and hazard ratio 1.11, 95% CI, 1.06 to 1.165] 16 . Nevertheless, when only studies using a sibling-matched design were analysed, this meta-analysis concluded that there was no significant association (hazard ratio 1.07, 95% CI, 0.99 to 1.16), 13,16 whereas another demonstrated a significant association in sibling-matched designed studies [hazard ratio 1.10, 95% CI, 1.02 to 1.18], 13 with, however, no dose–response effect. It was concluded that the small statistically significant association between LEA and ASD may be elucidated by selection bias and residual (unmeasured) confounders, such as genetic factors 16 …”
mentioning
confidence: 94%
“…Meta-analyses conducted on this topic present an intriguing picture. [13][14][15][16] On one hand, they reveal an association between neuraxial labour analgesia and autism when no confounding variables are considered. However, a critical turning point emerges when confounders are pondered, resulting in a very weak association.…”
mentioning
confidence: 99%
See 2 more Smart Citations